Assessment of the knowledge and perceptions of the Malaysian community pharmacists regarding pharmacovigilance: findings from an interventional study - Elkalmi, Ramadan Mohamed Mahmod; Hassali, Mohamed Azmi; Mohamed Izham, Mohamed Ibrahim (Elsevier Inc., 2010)
OBJECTIVES: To assess the knowledge and perception of community pharmacists in Malaysia toward reporting of adverse drug reactions (ADRs). METHODS: A crosssectional study employing pre and post intervention design was undertaken with a sample of 42 community pharmacists to explore their knowledge of and the perception toward the pharmacovigilance and ADRs reporting. Changes in scores before and after the completion training program in knowledge and perception were measured. Statistical analysis: The data were analyzed by using SPSS version 17.0 software package (SPSS Inc., Chicago, IL, USA). Both descriptive and inferential statistics were used when ever appropriate. Frequencies and percentages were used to describe the respondents’ demographic information and professional characteristics. Wilcoxon Signed ranks test, Paired sample t test and The McNemar χ 2 test were applied to compare the differences in knowledge and perception before and after the educational program whenever appropriate. RESULTS: Forty-two community pharmacists (CPs) were enrolled in this study. A comparison of CPs knowledge before and immediately after implementation the education program showed signiﬁ cant differences, the participated community pharmacists’ mean scores in knowledge of pharmacovigilance and adverse drug reactions reporting signiﬁ cantly increased compared to the baseline (z